Analysing behavioural intentions of Indian consumers towards Digital banking - Kumar Singh, Amit; Shrivastav, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
Background: Thanks to the liberalization, privatization, and globalization measures initiated by the Government of India under its new economic policy regime, India is witnessing a boom in the global market. This scenario has enhanced the need for understanding the product adoption behavior that would enable the marketers to arrive at strategies corresponding to the target markets socio-economic, political, cultural, and competitive setting at the macro level and an adopter-centered approach at the micro level. Adoption is the decision of a prospective buyer to become a regular user of the product. Aims: Indian consumers too have access to many new channels to interact with their bank. Banks race against each other in bringing the latest technology for the benefit of their customers and themselves. But not many studies have been conducted to evaluate if the “digital banking” channel is utilized properly by the customers in India. Reasons for customer apathy towards digital banking channels, if that exists, have also not been analyzed in an Indian context earlier. Methodology: Both exploratory and descriptive research designs were used in this research paper, which included a field survey where the researcher went to the population of interest for them to describe and interrupt problems that are typical of normal conditions, attitudes, beliefs, practices, and targets/aims about internet banking usage to establish the status of the problem under investigation. Results/Findings: A multiple regression model will test the assumptions required to ensure the validity of its significance test. This will help us check for a statistically significant relationship. Other statistical techniques used for analyzing the data collected will also be discussed. In the context of the findings of the study, data analyses will be reported. Conclusions: Most consumers form expectations of the service product, banking service provider, service, and quality of the product that they patronize before engaging in banking activities. These expectations influence their attitudes and intentions to get facilitated banking services through a certain bank and consequently their decision-making processes, purchasing behavior, and loyalty as well.